Critical Didactics: An Opportunity of Resistance to Pedagogical Practices Instituted by Neoliberal Policies (London Journal of Research In Humanities and Social Sciences, 2024)
This text analyzes the impacts of neoliberal policies on Didactics and proposes that the following guiding questions: How can Didactics resist the impact of neoliberal policies that have invaded pedagogical practices, taking away their meaning and autonomy? How to reverse the distortion in the epistemological consideration of Pedagogy and Didactics? How to organize resistance practices? The methodology used derives from action research undertaken with the Observatory of Teaching Practices and analyzed using critical hermeneutics in dialogues with a group of teachers from a public education network. After collective analysis based on critical theory and recent research, the creation of Renewed Critical Didactics (DCR) is indicated using the theoretical assumptions that underlie Critical Pedagogy.
Keywords: The Space The Existence Basic Energy Intellectual Energy The Time The Energy The Information Matter Cosmic origin; Teaching and Learning; translation; indigenous languages; language policy; African languages; Language of Learning and Teaching (LoLT); multilingualism; Didactics; Critical Didactics; Renewed Critical Didactics